Analysts' Selective Coverage and Subsequent Performance of Newly Public Firms - DAS, SOMNATH; GUO, RE‐JIN; ZHANG, HUAI (Journal of Finance, 2006)
ABSTRACT This study examines the ability of analysts to forecast future firm performance, based on the selective coverage of newly public firms. We hypothesize that the decision to provide coverage contains information about an analyst's underlying expectation of a firm's future prospects. We extract this expectation by obtaining residual analyst coverage from a model of initial analyst following. We document that in the three subsequent years, initial public offerings with high residual coverage have significantly better returns and operating performance than those with low residual coverage. This evidence indicates analysts have superior predictive abilities and selectively provide coverage for firms about which their true expectations are favorable.